MITOLOGI DAN PENDIDIKAN KARAKTER DALAM TRADISI MEMBUAT COK BAKAL TAKIRAN MACAPAT DI KABUPATEN MOJOKERTO - Wahyu Budi Utami (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2019)
The aim of this research is to describe the tradition of the Macapat Tak estimation in Mendek Village, and to identify the myths contained therein by using mythological studies which include markers and markers and the value of character education in them. This research takes the object of tradition to make a macapat rice cake in Mendek Village, Mojokerto Regency. Research data can be obtained using the method of observation, documentation and interviews. The subjects of this study were Mendek village elders and Mendek residents. This study was analyzed through the stages of data reduction, data verification, and data display. The results showed that there was a process of carrying out the tradition of making mac chapters in Macapat estimation in Mendek Village. The type of offerings in the tradition of making macapat will assess macapat by having eleven kinds namely cone, egg, setaman flower, spices, sengkolo porridge, tape, and sticky rice which have signs, markers and markers inside. Furthermore, five values ??of character education are found, namely religious values, values ??of responsibility, communicative values, values ??of caring for the environment, and values ??of patriotism. Keywords: Mythology, Chocolate Will Takiran Macapat, Value of Character Education